Analisis Pengaruh Paparan Konten Negatif di Media Sosial Terhadap Kesehatan Mental Gen Z - Henisa Sabillillah; Tata Sutabri (Institut Nalanda, 2025)
Social media has become an inseparable part of Gen Z's daily life. However, despite its benefits, exposure to negative content on social media can adversely affect mental health. This study aims to analyze the extent to which exposure to negative content influences Gen Z's mental health. The research employs a quantitative approach by surveying 300 respondents aged 18–25 in Indonesia. The findings reveal a significant correlation between exposure to negative content, such as cyberbullying, fake news, and body shaming, and higher levels of anxiety, depression, and stress. This article provides insights for policymakers and society to create a healthier social media ecosystem, emphasizing the importance of digital literacy, content moderation, and stricter regulations to mitigate harmful content exposure.